A Three-Dimensional Cu(II)-MOF with Lewis acid−base dual functional sites for Chemical Fixation of CO2 via Cyclic Carbonate Synthesis. Issue 39 (July 2020) - Gupta, Anoop K.; Guha, Nikita; Krishnan, Sarathkumar; Mathur, Pradeep; Rai, Dhirendra K.
Graphical abstract: A 3D porous inorganic-organic hybrid; Cu(II)-MOF (1 ), having Lewis acid − base dual-functional sites, has been utilized for chemical fixation of CO2 with various epoxides to useful chemical cyclic carbonates, under mild and solvent free conditions. Highlights: A 3D porous Cu(II)-MOF, having Lewis acid− base dual-functional sites, has been explored for cycloaddition of CO2 with epoxide in the presence of TBAB co-catalyst. The weakly basic piperazine functionalities of the linker, by offering CO2 concentration effect, and suitably oriented Lewis acidic Cu 2+ in the channels of MOF collectively show an excellent catalytic performance towards fixation of CO2 to value-added products, cyclic carbonates. The present MOF shows robust framework integrity and displays excellent recyclability without apparent loss of catalytic activity. Abstract: A 3D porous Cu(II)-MOF (1 ), having Lewis acid− base dual-functional sites, has been utilized, whose frameworks have two types of 1D channels decorated with both axially water-bound metal sites and weak base, i.e., tertiary amine groups in the crystallographic c -axis. Upon activation under a high vacuum at 120 °C, the axial water molecule is removed and affords a solvent-free and unsaturated Lewis acidic Cu(II) containing framework (1′ ). The piperazine functionalities from the linkers enhance the selective adsorption of CO2 which, in turn, facilitate the further interaction with the open Cu(II) metal centres, leading to catalytic chemical fixation of CO2 into five-membered cyclic carbonates, in the presence of epoxides and co-catalyst TBAB, under mild and solvent-free reaction conditions. The significance of dual functionalization and the synergy with TBAB on adeptly catalyzed CO2 fixation are explored using several epoxides, and substantial conversion is achieved. Moreover, the catalyst 1′ displays satisfactory stability and easy recyclability for five consecutive cycles without any appreciable loss in its catalytic activity. The results are compared with various MOFs based catalysts at the closest reaction conditions and, based on literature and experimental inferences, a possible mechanism of chemical fixation of CO2 with epoxide catalyzed by 1′ has been proposed.